Association of 10 single nucleotide polymorphism loci with nicotine addiction in the Anatolian population? - Emel Hulya Yukseloglu; Alpen Ortug; Gulten Rayimoglu; Fatma Cavus Yonar; Itir Erkan; Umut Kara; Dilek Salkim Islek; Melek Ozlem Kolusayin Ozar; Kadir Dastan; Omer Karatas (Biotechnology & Biotechnological Equipment, 2019)
The study aimed to discover some variables influencing the risk of nicotine dependence in the Anatolian population. We examined 10 candidate genes and analysed 10 single nucleotide polymorphism (SNP) loci in 50 cases and 50 controls in a preliminary study. The main purpose of this work was to provide predicative definition in this regard. Buccal swab samples were collected from 50 cases and 50 controls, who had volunteered to participate in the study. The Fagerström Test for Nicotine Dependence (FTND) score of 4 or more was required for the case group. The control group was strictly chosen from people who had an FTND score of 0. SNP loci were genotyped and variations were observed in five SNP loci (rs16969968, rs806380, rs3733829, rs6474412, rs1329650). Based on these results, polymorphism was identified in the Turkish population in five SNP loci (rs16969968, rs806380, rs6474412, rs37333829, rs1329650). Although our findings indicated a non-significant association between the 10 selected loci and nicotine dependence in the Anatolian population, we believe that with a larger number of cases with five SNP loci, the variance we find will provide significant results for both forensic geneticists and psychiatrists. Since, to our knowledge, this is the first work to explore the potential association of these SNPs with nicotine addiction in the Anatolian population, the results should be expanded with larger sample groups.